Emerging insights into the immunosuppressive tumor microenvironment and its implications for glioblastoma immunotherapy - Nicolaou, Niovi; Andreou, Maria S.; Neophytou, Christiana M.; Papageorgis, Panagiotis (Frontiers in Immunology, 2025)
Glioblastoma is considered the most common and lethal form of brain cancer. Despite tremendous progress in glioblastoma therapeutics, the profound intra- and inter-tumoral heterogeneity of glioblastoma tumors, the difficulty of agents to cross the blood-brain barrier (BBB), the development of drug resistance as well as the immunosuppressive tumor microenvironment (TME) predominantly account for the failure of existing conventional and targeted therapies. Therefore, there is a growing necessity to decipher the complexity of the TME that promotes immunosuppression and to discover innovative strategies targeting both the tumor and its TME to improve patient treatment outcomes. In this comprehensive review, we present the latest evidence implicating various components of the TME in regulating the efficacy of immunotherapies. We also discuss the current challenges and opportunities of immunotherapy in treating glioblastoma, including ongoing clinical trials using immune checkpoints inhibitors (ICIs), CAR-T cell therapy, vaccines, cytokine therapy and oncolytic viruses.